2001
DOI: 10.1073/pnas.211178398
|View full text |Cite|
|
Sign up to set email alerts
|

Photochemically enhanced binding of small molecules to the tumor necrosis factor receptor-1 inhibits the binding of TNF-α

Abstract: The binding of tumor necrosis factor alpha (TNF-α) to the type-1 TNF receptor (TNFRc1) plays an important role in inflammation. Despite the clinical success of biologics (antibodies, soluble receptors) for treating TNF-based autoimmune conditions, no potent small molecule antagonists have been developed. Our screening of chemical libraries revealed that N -alkyl 5-arylidene-2-thioxo-1,3-thiazolidin-4-ones were antagonists of this protein–protein interaction. After chemical optimization,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
52
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(52 citation statements)
references
References 27 publications
0
52
0
Order By: Relevance
“…18 Second, ligand-therapy is a potential option, because inhibitors or modulators of TROY signaling or expression may reduce tumor growth. [46][47][48][49] Finally, it may be possible to detect circulating TROY-expressing melanoma cells in serum using RT-PCR-based techniques. MITF in particular has already showed some promise as a single marker in this regard 39,50 but with TROY, specific immunological detection of melanoma cells rather than their lessspecific secreted antigens 51 may also be feasible.…”
Section: Discussionmentioning
confidence: 99%
“…18 Second, ligand-therapy is a potential option, because inhibitors or modulators of TROY signaling or expression may reduce tumor growth. [46][47][48][49] Finally, it may be possible to detect circulating TROY-expressing melanoma cells in serum using RT-PCR-based techniques. MITF in particular has already showed some promise as a single marker in this regard 39,50 but with TROY, specific immunological detection of melanoma cells rather than their lessspecific secreted antigens 51 may also be feasible.…”
Section: Discussionmentioning
confidence: 99%
“…But the desired antibody could not be created, because the anti-TNFR1 antibodies recognizing the TNF-binding site on TNFR1 acted like a TNFR1 agonist and not an antagonist (22). Attempts to design a low molecular weight TNFR1 antagonist based on the three-dimensional structural information of the TNFR1 was also not successful in identifying an antagonist that would selectively inhibit the TNF/TNFR1 interaction and would have sufficient therapeutic effect (23,24). In this respect, we previously 1) constructed two phage libraries displaying the structural TNF variants in which six amino acid residues (amino acids 29, 31, 32, 145-147, library I; amino acids 84 -89, library II) in the predicted receptor binding sites were replaced with other amino acid, 2) and we successfully identified the TNFR1-selective mutant with great biological activity from the library I.…”
Section: Tumor Necrosis Factor (Tnf)mentioning
confidence: 99%
“…Compound 769078 represents group C dual inhibitors containing a rhodanine moiety linked to furan ring by an alkene spacer. Rhodanine is a known pan assay-interference moiety (Mendgen et al, 2012) that has been reported active in a significant number of HTS assays, causing concerns about the specificity of compounds containing this chemical group (Carter et al, 2001;Voss et al, 2003;Carlson et al, 2006;Powers et al, 2006;Baell and Holloway, 2010). However, these compounds share the common features seen in other DNPEP inhibitors with two functional groups bridged by four to six covalent bonds, suggesting that they could exert a DNPEP-selective effect with further modifications.…”
mentioning
confidence: 99%